Fundamental pattern movement influences in volleyball learning skills - Krug, A. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction The objective of the study was to investigate if Fundamental Pattern Movement (FPM: strike, jump, axial movements, balance, volleying, throwing and displacement) show better results in Volleyball skills (service, spike, forearm and overhand pass) on quantitative and qualitative results. Methods This is a quasi-experimental type of study with 41 students from two intact classes from a public school in Cruz Alta, RS, Brazil. The controlled variables were age, gender, grade and no previous Volleyball learning experience and teacher comportment process. Students were submitted to a pre-test in Volleyball skills. After this fifteen classes (50 minutes each) with the same teacher were developed. To the experimental group 1 (EG1) was applied FPM and to the EG2 only Volleyball skills. A retest was applied and more fifteen-lesson classes were developed with teacher and content controls, and a posttest. The data were treated with SPSS/PC and dependent Student t Test. Results Both Groups improved Volleyball skills after the treatments, however no significant differences were found between EG1 and EG2 after retest. Posttest showed quantitative significant differences in service and spike favorable to EG1. Conclusion FPM treatment showed better quantitative results in some but not all Volleyball skills, however the same did not occurred at the qualitative results. More studies are needed to clarify these findings.